Enhancement Integrated Quality Management in Islamic Education Institutions - Asnawan, Asnawan (Bulletin of Science Education, 2021)
The article descibed total quality management in islamic education institutions. Teamwork in handling projects of improvement or development of the quality of education is done through empowerment (empowerment) employees and its working groups by giving greater responsibility. The researchers used library research that carried out on several data findings from literature sources of well-known journal publications such as Google Book, Google Scholar, Taylor & France, Elsevier, and other publications that discuss issues of total quality management. To get answers to the problems of this study, the researchers involve a coding system, data interpretation, and high-level evaluation to get valid and reliable data. The result showed that the existence of cooperation in an educational institution is the main capital in achieving quality and stakeholder satisfaction through a process of continuous quality improvement. Teachers, staff and everyone in educational institutions also provide services to their colleagues and fellow internal customers. Poor internal relations would be hinder the development of an institution. Total Quality Management (TQM) is transforming a school institution into a team to achieve a single goal of satisfying all customers. The role of parents in children's self-motivation from an early age is a big asset for children's success in school. Keywords: Integrated Quality Management, Total Quality Management, Quality Management Institution